PENGEMBANGAN MUTU DIRI GURU - Eliterius Sennen (JIPD (Jurnal Inovasi Pendidikan Dasar), 2017)
As it is generally known that a teacher is a key element who determines success of teaching-learning enterprises. A qualified education is mostly affected by a qualified teacher. Therefore, teachers are required to develop self-quality. Teacher Forum (MGMP) and Teacher Group Work (KKG) are the vessels for them to enhance the quality. This writing seeks to discuss the implementation of those existing programs in the attempt to the development of teacher-self quality.